Think Raku How to Think Like a Computer Scientist - Rosenfeld, Laurent; Downey, Allen B. (Open textbook library., 2017)
The title of this book was originally Think Perl 6, but since Perl 6 has been renamed Raku, we have also changed the title of the book. Think Raku is an introduction to computer science and programming intended for people with little or no experience. This aim of this book is not primarily to teach Raku, but instead to teach the art of programming, using the Raku language. After having completed this book, you should hopefully be able to write programs to solve relatively difficult problems in Raku, but my main aim is to teach computer science, software programming, and problem solving rather than solely to teach the Raku language itself. Think Raku is a free book available under a Creative Commons license. Readers are free to copy and distribute the text; they are also free to modify it, which allows them to adapt the book to different needs, and to help develop new material.